2016
DOI: 10.3390/ijms17111962
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Secondary-Structure Folding on the Mutually Exclusive Folding Process of GL5/I27 Protein: Evidence from Molecular Dynamics Simulations

Abstract: Mutually exclusive folding proteins are a class of multidomain proteins in which the host domain remains folded while the guest domain is unfolded, and both domains achieve exchange of their folding status by a mutual exclusive folding (MEF) process. We carried out conventional and targeted molecular dynamics simulations for the mutually exclusive folding protein of GL5/I27 to address the MEF transition mechanisms. We constructed two starting models and two targeted models, i.e., the starting models GL5/I27-S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The RMSD value of the DPP‐IV–YPVEPFT complex is higher than those of the other three complexes, which indicates that DPP‐IV–LDADGSY, DPP‐IV–FNPTY, and DPP‐IV–SPPEFLR complexes are more stable. Rg is often used to study the tightness of protein structures, and the degree of the unfolding of proteins is proportional to the Rg value (Wang et al., 2016). Figure 6B shows that the tightness of the DPP‐IV–peptide complex changes significantly upon binding, with YPVEPFT exhibiting higher Rg values, which represent the maximum unfolding of the peptide.…”
Section: Resultsmentioning
confidence: 99%
“…The RMSD value of the DPP‐IV–YPVEPFT complex is higher than those of the other three complexes, which indicates that DPP‐IV–LDADGSY, DPP‐IV–FNPTY, and DPP‐IV–SPPEFLR complexes are more stable. Rg is often used to study the tightness of protein structures, and the degree of the unfolding of proteins is proportional to the Rg value (Wang et al., 2016). Figure 6B shows that the tightness of the DPP‐IV–peptide complex changes significantly upon binding, with YPVEPFT exhibiting higher Rg values, which represent the maximum unfolding of the peptide.…”
Section: Resultsmentioning
confidence: 99%
“…This parameter is often employed to investigate the tightness of the protein structure. A higher R g value indicates higher degree of protein unfolding (Wang et al, 2016). As shown in Figure 4c, the tightness of ACE–peptide complexes changed significantly after binding, consistent with the variation trend of SASA.…”
Section: Resultsmentioning
confidence: 99%
“…This parameter is often employed to investigate the tightness of the protein structure. A higher R g value indicates higher degree of protein unfolding (Wang et al, 2016).…”
Section: Simulation Studiesmentioning
confidence: 99%
“…The radius of gyration ( R g ) was used to describe the tightness of the protein structure. The greater the value, the higher the degree of protein unfolding [43]. The data in Figure 8C indicated that the average R g of the ACE−peptide complex system was indistinguishable from the receptor ACE itself, indicating that the tightness of ACE did not change significantly after binding Ile-Ile-Tyr and Asn-Pro-Pro-Lys, and remained stable.…”
Section: Resultsmentioning
confidence: 99%